2023
DOI: 10.1002/jum.16223
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariable Model Based on Ultrasound Imaging Features of Gastrocnemius Muscle to Identify Patients With Sarcopenia

Abstract: ObjectivesLow skeletal muscle mass, strength, or somatic function are used to diagnose sarcopenia; however, effective assessment methods are still lacking. Therefore, we evaluated the effectiveness of ultrasound in identifying patients with sarcopenia.MethodsThis study included 167 patients, 78 with sarcopenia and 89 healthy participants, from two hospitals. We evaluated clinical factors and five ultrasound imaging features, of which three ultrasound imaging features were used to create the model. In both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(109 reference statements)
0
0
0
Order By: Relevance
“…21 Previous studies demonstrated that ultrasound measurement of gastrocnemius muscle could identify sarcopenia in hospitalized patients older than 60 years. 33 Considering that the gastrocnemius muscle was more readily available than the quadriceps, we chose gastrocnemius muscle as the measured muscle. Similarly, we found that type 2 diabetic patients with sarcopenia had lower CSA, MT and SWE values than patients without sarcopenia, and we also developed a diagnostic model for sarcopenia using age, CSA and SWE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Previous studies demonstrated that ultrasound measurement of gastrocnemius muscle could identify sarcopenia in hospitalized patients older than 60 years. 33 Considering that the gastrocnemius muscle was more readily available than the quadriceps, we chose gastrocnemius muscle as the measured muscle. Similarly, we found that type 2 diabetic patients with sarcopenia had lower CSA, MT and SWE values than patients without sarcopenia, and we also developed a diagnostic model for sarcopenia using age, CSA and SWE.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to a decrease in the number of muscle fibers and an increase in the amount of connective tissue such as adipose and extracellular matrix in patients with sarcopenia, resulting in a more significant decrease in muscle stiffness in patients with sarcopenia. 33,38 SWE, which spatially represents soft tissue stiffness and measures muscle quality, appears to be a reliable technique for assessing muscle fibrosis in sarcopenia. Cr is an endogenous product released by muscle, and its blood concentration depends on muscle mass.…”
mentioning
confidence: 99%